2012
DOI: 10.1186/1749-799x-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb joint replacement in rheumatoid arthritis

Abstract: IntroductionThere is limited literature regarding the peri-operative and surgical management of patients with rheumatoid disease undergoing lower limb arthroplasty. This review article summarises factors involved in the peri-operative management of major lower limb arthroplasty surgery for patients with rheumatoid arthritis.MethodsWe performed a search of the medical literature, using the PubMed search engine (http://www.pubmed.gov). We used the following terms: ‘rheumatoid’ ‘replacement’ ‘arthroplasty’ and ‘o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
0
24
1
2
Order By: Relevance
“…The literature contains few references to the influence of psychological factors on the results of surgical management. A recent systematic review of factors involved in the perioperative management of major lower limb arthroplasty found that RA patients with clinical depression do not improve to the same extent as those without [46].…”
Section: C Psychological Factors Influencing the Effectiveness Of mentioning
confidence: 99%
“…The literature contains few references to the influence of psychological factors on the results of surgical management. A recent systematic review of factors involved in the perioperative management of major lower limb arthroplasty found that RA patients with clinical depression do not improve to the same extent as those without [46].…”
Section: C Psychological Factors Influencing the Effectiveness Of mentioning
confidence: 99%
“…Other causes of reduced bone stock (such as rheumatoid arthritis, osteoporosis and steroid use) also increase the risk of periprosthetic fracture [ 9 ]. In studies of joint registries, rheumatoid arthritis increases the risk of periprosthetic fracture by a factor of between 1.5 and 2.1 [ 16 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Surgeons and anesthesiologists alike must be aware of the increased risk to the cervical spine as 80% of patients have atlantoaxial instability [4]. The cervical spine also is at elevated risk of basilar invagination and subaxial instability, and thus preoperative radiographic investigation via flexion and extension images should be obtained, as intubation for surgery can often require hyperextension of the patient's neck, and should be avoided should instability be present [5].…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Controversy exists on whether upper or lower extremity pathology should be addressed first. Clement et al argue that stresses placed on the upper extremity during therapy for TKA may further damage previously repaired joints [4]. Conversely, Chmell et al believe that upper extremity impairment such as severe wrist pain due to RA may impair lower extremity rehabilitation, and thus wrist fusion should be considered prior to TKA.…”
Section: Preoperative Considerationsmentioning
confidence: 99%